2013
DOI: 10.1177/1069072713515843
|View full text |Cite
|
Sign up to set email alerts
|

Profiling the Multiple Role Planning Attitudes of College Women

Abstract: We conducted a latent profile analysis of scores on a measure of multiple role planning attitudes obtained from an ethnically diverse sample of undergraduate women (age range: 18–29 years) to determine whether clusters of participants with distinct profiles of these attitudes were identifiable and whether these groups differed with respect to their educational level, relationship commitment status, and in their responses to independent measures of their relationship dispositions and orientations. Findings yiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Unlike for prior generations, there is no clear demarcation of labor in the family and work domains, and women no longer solely dedicate their lives to childcare and household works while men earn money for the family (Peake & Harris, 2002). Contemporary young men and women believe in the importance of engaging multiple roles without interrupting any singular role’s responsibilities (Kerpelman & Schvaneveldt, 1999; Lopez et al, 2014; Peake & Harris, 2002). In addition, both genders already understand some of the challenges that they will face to balance their work and nonwork lives in the future (Weer, Greenhaus, Colakoglu, & Foley, 2006).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike for prior generations, there is no clear demarcation of labor in the family and work domains, and women no longer solely dedicate their lives to childcare and household works while men earn money for the family (Peake & Harris, 2002). Contemporary young men and women believe in the importance of engaging multiple roles without interrupting any singular role’s responsibilities (Kerpelman & Schvaneveldt, 1999; Lopez et al, 2014; Peake & Harris, 2002). In addition, both genders already understand some of the challenges that they will face to balance their work and nonwork lives in the future (Weer, Greenhaus, Colakoglu, & Foley, 2006).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…As argued by Arnett (2004), emerging adults (aged 18–25) have an enhanced ability to manage their time and money and to explore their identities in career, marriage, finance, parenting, and other role responsibilities. In contrast to previous generations, both young men and women anticipate participating in both a career and family (Lopez, McDermott, & Fons-Scheyd, 2014; Peake & Harris, 2002). On the other hand, some research have shown that both genders in young age often fail to plan practically for future role balance, while other studies have discussed the normative controls that could affect peoples’ role balance intentions (Stevens, Puchtell, Ryu, & Mortimer, 1992).…”
mentioning
confidence: 99%
“…Thus, the within-group differences for young women who did not enter college or attended community college remains virtually unknown (see Robinson et al, 2003 for an exception). What we do know is that college women may be anticipating career barriers while making career decisions ahead of actually experiencing them (Gregor & O’Brien, 2015; Lopez et al, 2014; McCracken & Weitzman, 1997; O’Brien et al, 2000) and that these barriers might be more strongly felt for minoritized women (Baker et al, 2016; C. Brown et al, 2012; Lopez & Ann-Yi, 2006; Piña-Watson et al, 2014; Savela & O’Brien, 2016), although women who were nontraditional college students appeared to report few career barriers when social support was adequate (Breese & O’Toole, 1995; Quimby & O’Brien, 2004).…”
Section: Research Findingsmentioning
confidence: 99%
“…That systemic, role-related inequalities elevate stress more than isolated, short-term incidents (Kahn, et al, 1964) is a well-established pattern that may help explain why people who identify with a socially marginalized group, on average, have higher probabilities of anxious or depressive symptoms. Originally introduced to understand "felt difficulty in fulfilling role obligations" (Moore, 1960), psychologists and sociologists have used role strain theory to understand role conflict (Davis, 2013;Lopez et al, 2014), social participation and mental health (Shiba et al, 2017) and leadership in diverse communities (Edwards, 2014). This work is sensitive to people's multiple social identities and the meanings that identities take on within their social contexts.…”
Section: Role Strainmentioning
confidence: 99%